A Review of the Metabolism of 1, 4‐Butanediol Diglycidyl Ether–Crosslinked Hyaluronic Acid Dermal Fillers. Issue 12 (13th August 2013) - De, Koenraad; Glogau, Richard; Kono, Taro; Nathan, Myooran; Tezel, Ahmet; Roca‐Martinez, Jean‐Xavier; Paliwal, Sumit; Stroumpoulis, Dimitrios
<x xml:space="preserve">Abstract</x> Background Cosmetic procedures are growing ever more common, and the use of soft tissue fillers is increasing. Practicing physicians need to be aware of the biological behavior of these products in tissue to enable them to respond to any safety concerns that their patients raise. Objectives To provide an overview of the metabolism of 1, 4‐butanediol diglycidyl ether (BDDE)‐crosslinked hyaluronic acid (HA) dermal fillers and to examine the safety of the resulting byproducts. Methods A review of available evidence was conducted. Results After reaction with HA, the epoxide groups of BDDE are neutralized, and only trace amounts of unreacted BDDE remain in the product (<2 parts per million). When crosslinked HA, uncrosslinked HA, and unreacted BDDE degrade, they break down into harmless byproducts or into byproducts that are identical to substances already found in the skin. Conclusion Clinical and biocompatibility data from longer than 15 years support the favorable clinical safety profile of BDDE‐crosslinked HA and its degradation products. Given the strength of the empirical evidence, physicians should be confident in offering these products to their patients.